D27‐LIKE1 isomerase has a preference towards trans/cis and cis/cis conversions of carotenoids in Arabidopsis. (21st November 2022) - Gulyás, Zsolt; Moncsek, Blanka; Hamow, Kamirán Áron; Stráner, Pál; Tolnai, Zoltán; Badics, Eszter; Incze, Norbert; Darkó, Éva; Nagy, Valéria; Perczel, András; Kovács, László; Soós, Vilmos
SUMMARY: Carotenoids contribute to a variety of physiological processes in plants, functioning also as biosynthesis precursors of ABA and strigolactones (SLs). SL biosynthesis starts with the enzymatic conversion of all‐ trans ‐β‐carotene to 9‐ cis‐ β‐carotene by the DWARF27 (D27) isomerase. In Arabidopsis, D27 has two closely related paralogs, D27‐LIKE1 and D27‐LIKE2, which were predicted to be β‐carotene‐isomerases. In the present study, we characterised D27‐LIKE1 and identified some key aspects of its physiological and enzymatic functions in Arabidopsis. d27‐like1‐1 mutant does not display any strigolactone‐deficient traits and exhibits a substantially higher 9‐ cis ‐violaxanthin content, which is accompanied by a slightly higher ABA level. In vitro feeding assays with recombinant D27‐LIKE1 revealed that the protein exhibits affinity to all β‐carotene isoforms but with an exclusive preference towards trans/cis conversions and the interconversion between 9‐ cis, 13‐ cis and 15‐ cis ‐β‐carotene forms, and accepts zeaxanthin and violaxanthin as substrates. Finally, we present evidence showing that D27‐LIKE1 mRNA is phloem mobile and D27‐LIKE1 is an ancient isomerase with a long evolutionary history. In summary, we demonstrate that D27‐LIKE1 is a carotenoid isomerase with multi‐substrate specificity and has a characteristic preference towards the catalysation of cis/cis interconversion of carotenoids. Therefore, D27‐LIKE1 is a potential regulator of carotenoid cis pools and, eventually, SL and ABA biosynthesis pathways. Significance Statement: We demonstrate that DWARF27 (D27)‐LIKE1, a paralog of the strigolactone (SL) biosynthesis enzyme D27, is a carotenoid isomerase with multi‐substrate specificity and a characteristic preference towards the catalysation of cis – cis interconversion of carotenoids. The enzyme functionally diverged from its paralog with a primary role in 9‐ cis ‐violaxanthin isomerisation and is a potential regulator of carotenoid cis pools and eventually, SL and ABA biosynthesis pathways.